Use of Web-GIS Database Model to Accommodate Public Participation in the Improvement of Sustainable Road and Bridge Management: A Conceptual Idea - Demon, Stephanus Ola; Nani, Paskalis Andrianus; da Costa, Don Gaspar Noesaku (JUTEKS : Jurnal Teknik Sipil, 2024)
Sustainability is usually associated with energy source, ecological, soil and environmental aspects. Periodical road and bridge preservation is required to ensure the increasing of accessibility and mobility level, to increase regional economics’ growth, to minimize unplanned or unpredicted environmental consequences and to improve institutional arrangement capability as well. Road and bridge preservation is commonly managed based on its level of damage and constrained in budgeting. Poor public policy makes it worst. Therefore, the issue of strengthening the capacity of regional road and bridge management institutions is deemed important and urgent not only to reduce roads and bridges preservation cost but also to increase regional economics’ growth. Therefore, a proper road preservation type and priority should be determined based on technical, socio-economics, environment and public policy consideration. However, annual road and bridge functional condition data collection took high cost because it has been carried out by engineering consultant. The aim of this study is resolve it by providing a public participation portion in a road and bridge data base model. They are simply asked to send a real time condition of road s or bridge nearby to the local authority. The results strongly indicate that cost saved obtained from it could be focused to road and bridge preservation cost.